A poster of the Velankanni Matha on the door of a Koli home - Mumbai Archive Project Team (Jio Institute, 2024)
Christian Koli homes feature religious icons such as the holy cross, Jesus, and Mother Mary placed above doors and entrances. This residence has a poster of the Velankanni Matha, commonly known as our Lady of Good Health. As a way of assimilation into local traditions, the Velankanni Matha is draped in a saree, following Indian custom.